Enhancing English Language Proficiency (Language Skills) through YouTube: A Systematic Review (Research Journal on Multi-disciplinary Issues, 2026)
The systematic review examines 20 international studies (2020-2025) on the YouTube's role in enhancing English language skills: listening, speaking, reading and writing in EFL/ESL context across Indonesia, Vietnam, Peru, Saudi Arabia and Malaysia. Most of the studies are in the context of Indonesia. This study follows the PRISMA 2020 guidelines and this review reveals that YouTube significantly enhances and improves listening, speaking, reading and writing skills with better progress in vocabulary, pronunciation, and fluency and learner motivation. These 20 articles reveal that they are highly constructive and supportive, reporting significant benefits for reading and writing through multimedia-supported vocabulary development, retention, and writing creativity. The finding highlights that YouTube as an effective, flexible tool that supports autonomous and interactive learning, emphasizing the needs for strategic integration and digital literacy to maximize its educational impact.